Post-cholecystectomy Gallstone Ileus. Issue 6 (June 2020) - Meier, Jennie; Guzzetta, Angela A.; Huerta, Sergio
Gallstone ileus is an unusual complication of cholelithiasis. Classically, a stone is impacted at the terminal ileum originating from a cholecystoduodenal fistula. Exceptions to this pathophysiology have been noted at each step. In this systematic review, we document a comprehensive review of postcholecystectomy gallstone ileus inclusive of 49 separate cases and report 8 different mechanisms leading to this unusual complication. The most common mechanism is a lost stone during cholecystectomy that then erodes through the intestinal wall leading to bowel obstruction. Our review showed an older, female predominance (64.0%) at an average age of 68.0 years, patients typically had a burden of comorbidities. Delay in diagnosis was common (64% of cases) with the correct diagnosis made in 37.5% of patients during admission. Pneumobilia was commonly reported (29.0%). There was a wide range in the amount of time between cholecystectomy and gallstone ileus, from 10 days to 50 years (mean 12.4 years). Postcholecystectomy gallstone ileus is an unusual complication of cholelithiasis, which mandates surgery. Retrieval of stones should be undertaken if they are spilled during cholecystectomy. Owing to the increasing age of the American patient population, it is likely that a higher number of patients with this condition will be encountered.